2020
DOI: 10.1002/jgc4.1247
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives on the diagnostic journey to a monogenic diabetes diagnosis: Barriers and facilitators

Abstract: Approximately 2% of diabetes mellitus, or at least 500,000 cases in the United States, has a monogenic, rather than multifactorial, etiology (Hattersley et al., 2018; Pihoker et al., 2013). The most common form of monogenic diabetes is maturity-onset diabetes of the young (MODY), followed by neonatal diabetes and syndromic forms (ADA, 2016; Hattersley et al., 2018). Treatment options and prognoses for certain types of monogenic diabetes are distinct from those for type 1 and type 2 diabetes (T1D and T2D). Mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…As reported in other studies 12,14 , our participants also believed that genetic testing should play a central role in diabetes diagnosis, though they expressed limiting factors to its implementation. Consistent with the findings of previous workers [15][16][17] , and as viewed by most of our respondents, perhaps institutional training and education of HCPs in genetics was inadequate. Additionally, the lack of standard biomedical infrastructure and genomic expertise in services and research are known barriers to translational genomics in African countries.…”
Section: Genetics Knowledgesupporting
confidence: 89%
See 1 more Smart Citation
“…As reported in other studies 12,14 , our participants also believed that genetic testing should play a central role in diabetes diagnosis, though they expressed limiting factors to its implementation. Consistent with the findings of previous workers [15][16][17] , and as viewed by most of our respondents, perhaps institutional training and education of HCPs in genetics was inadequate. Additionally, the lack of standard biomedical infrastructure and genomic expertise in services and research are known barriers to translational genomics in African countries.…”
Section: Genetics Knowledgesupporting
confidence: 89%
“…Previous studies have identified a lack of knowledge and awareness among HCPs in Western nations as one of the barriers to genetic testing for MODY 14,15 . Low MODY knowledge and awareness among HCPs may also be contributing to the underdiagnosis of MODY in Africa, including Nigeria, but this has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, patients with GCK-MODY are not at increased risk for micro- or macrovascular complications of hyperglycemia ( 10 ) and thus do not require pharmacotherapy. Rather, treatment of their diabetes is often frustrating to patients as it results in either no improvement in their blood glucose or significant hypoglycemia ( 11 ). Accurate diagnosis of this condition prevents unnecessary treatment, as microvascular complications of GCK-MODY–related diabetes are exceedingly rare ( 6 ).…”
Section: Atypical Diabetesmentioning
confidence: 99%
“…Additionally, a document describing the variant identified and avenues for variant-specific testing can be provided to the patient to distribute to family members if family testing is being pursued. Upon reflecting on the diagnosis, patients may feel relief at a genetic etiology for their symptoms, while others may feel angry or annoyed if they were initially misdiagnosed and prescribed suboptimal treatment [72][73][74][75][76][77] . Feelings of frustration should be validated.…”
Section: Question 5: -How Should a Variant In A Monogenic Diabetes Ge...mentioning
confidence: 99%